Structure-function relationship studies in the disulfide-bond reductase DsbD and a c-type apocytochrome - Kritsiligkou, P (2011)
The efficient covalent attachment of heme to c-type apocytochromes in the periplasm of Gram-negative bacteria requires the provision of reductant. Heme attachment is facilitated by a system of eight proteins, the Cytochrome c maturation (Ccm) system. The disulfide bond oxidoreductase DsbD, a member of the Disulfide bond formation system (Dsb), transfers reductant to the Ccm system via interaction with one of its proteins, CcmG. This study is focused on two key proteins of these systems, the periplasmic disulfide bond oxidoreductase DsbD and a c-type apocytochrome, apocytochrome c-b562. A new method was established to assess the function of DsbD by linking it to the levels of c-type cytochrome maturation. This method was used to evaluate the activity of a range of DsbD variants. In addition, analysis of the biophysical properties of apocytochrome c-b562 was carried out using NMR spectroscopy. For this analysis, backbone assignments were completed for both oxidation states of the protein. Finally, studies aimed to determine the biophysical properties of the residues of the CXXCH heme binding motif were performed.